Accelerated in vitro model for occlusion of biliary stents: investigating the role played by dietary fibre - Surwase, Sachin; Balakrishnan, Harishankar; Acharya, Subrat K.; Makharia, Govind K.; Kumaraswamy, Guruswamy; Bhagavatula L. V. Prasad (BMJ Innovations, 2018)
ackground To develop a new accelerated in vitro model that has implications for investigating the mechanism of biliary stent occlusion and help in the development of new materials that can alleviate this problem. Methods We employ a combination of reconstituted animal bile, bacteria and cellulose fibres optimised to reproducibly generate accelerated occlusion of stents, and produce occlusions that closely mimic those found in clinical studies. Results Our model affords repeatable, highly accelerated occlusion (within 2–3 days, compared with between about a week to 2 months in previous models). Our results highlight the role of dietary fibre in blockage of stents and demonstrate their importance in the onset of occlusion. Conclusions This accelerated model may have implications for developing biliary stents with enhanced patency.